OPTIMALISASI KINERJA PEMASARAN MELALUI ORIENTASI KEWIRAUSAHAAN, ORIENTASI PASAR DAN INOVASI PRODUK PADA UMKM SEKTOR DAGANG DI KOTA SEMARANG - Hafizh Rifat Anandasutisna; Roymon Panjaitan; Amron; Mahmud (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
This study is motivated by the phenomenon of unstable marketing performance of MSME units in Indonesia and the inequality of MSME units in Semarang City, which reflects the urgency of strengthening marketing strategies. The study aims to analyze the influence of entrepreneurial orientation, market orientation, and product innovation on the marketing performance of trading-sector MSMEs. An explanatory quantitative approach was employed involving 130 MSME actors selected through purposive sampling. Data were analyzed using the PLS-SEM method with SmartPLS 4. The results indicate that entrepreneurial orientation and market orientation have a positive and significant effect on marketing performance, while product innovation has a positive but insignificant effect. These findings confirm that marketing performance is more influenced by the ability of business actors to be proactive, adaptive, and responsive to market needs rather than relying solely on product innovation. This study strengthens the Resource-Advantage Theory and provides practical guidance for the MSME sector and stakeholders in designing policies and marketing strategies oriented toward enhancing competitiveness and business sustainability